A multicenter, randomized controlled feasibility trial for the programs of the SoUth Korea study to PrEvent cognitive impaiRment and protect BRAIN health through lifestyle intervention in at‐risk elderly people (SUPERBRAIN): Prevention (nonpharmacological) / Multidomain. (7th December 2020) - Choi, Seong Hye; Jeong, Jee Hyang; Moon, So Young; Hong, Chang Hyung; Na, Hae Ri; Park, Yoo Kyoung; Park, Hee Kyung; Song, Hong Sun; Lee, Sun Min; Choi, Muncheong; Park, Kyung‐Won; Kim, Byeong C; et al.
Abstract: Background: Multidomain interventions can be useful for the prevention of dementia. We have developed the programs of SoUth Korea study to PrEvent cognitive impaiRment and protect BRAIN health through lifestyle intervention in at‐risk elderly people (SUPERBRAIN), which consists of a facility‐based (FMI) and a home‐based multidomain intervention (HMI) program suitable for elderly Koreans. This study aims to investigate the feasibility of the SUPERBRAIN programs before a large‐scale randomized controlled trial (RCT). Method: We recruited 152 participants from eight centers, among those without dementia aged 60‐79 years with at least one modifiable dementia risk factor. They were randomly assigned: 51 to the FMI arm, 51 to the HMI arm, and 50 to the control arm. The 6‐month multidomain intervention consisted of: management of metabolic and vascular risk factors, cognitive training and social activity, physical exercise, nutritional guidance, and motivational enhancement programs. The intervention program is determined feasible if the following success criteria are met: 1) a minimum retention rate of 75% at week 24; 2) a minimum adherence to the intervention program of 75%; and 3) at least no difference from the control arm in the change of the total scale index score of the Repeatable Battery for the Assessment of Neuropsychological Status from baseline to study end. Main secondary outcomes are disability, depressive symptoms, quality of life, vascular risk factors, physical performance, nutritional assessment, and motivation questionnaire. Result: Screening began in May 2019 and was completed in August 2019. The intervention is ongoing as planned. There were no significant differences in the bassline age (71.7 ± 4.8 vs. 70.9 ± 4.9 vs. 70.7 ± 4.8 years, p = 0.57) and level of education (10.2 ± 4.8 vs. 9.9 ± 5.2 vs. 10.5 ± 4.8 years, p = 0.82) among the FMI, HMI, and control arms. The proportion of women did not differ in FMI, HMI and control arms (72.5% vs. 72.5% vs.78.0%, p = 0.77). The study will be completed in March 2020. Conclusion: This study will inform the applicability of these multidomain intervention programs in at‐risk elderly people and contribute to the success of a subsequent RCT.